The Effect of Finger Painting Activities Using Natural Materials on the Creativity of Children Aged 5-6 Years - Siti Mahmudah; Khomsatul Jannah; Yunita Yunita (Universitas Negeri Makassar, 2022)
This study aims to examine the influence of finger painting activities in increasing the creative ability of students in the age group of 5-6 in Khadijah Dadapan Kindergarten. Quantitative research approach with quasi-experimental design type of research. The subjects of the study were ten children. The results of finger painting application to children's creativity are seen from the data description at the first meeting. As many as three children are in a good category, and seven are in a suitable type. The ability of children to make various forms using plasticine was met secondly, with six children in the excellent class and four in the good category. Indicators of children being able to paint using fingers with various new creations were obtained at the first meeting. Four children were in the excellent class, and six were in a suitable category. At the second meeting, eight children were of an appropriate type and two in a good variety. Thus, it was concluded that finger painting affected students' creativity in Khadijah Dadapan Kindergarten.